2014
DOI: 10.1111/jcmm.12351
|View full text |Cite
|
Sign up to set email alerts
|

iPSC‐derived human mesenchymal stem cells improve myocardial strain of infarcted myocardium

Abstract: We investigated global and regional effects of myocardial transplantation of human induced pluripotent stem cell (iPSC)-derived mesenchymal stem cells (iMSCs) in infarcted myocardium. Acute myocardial infarction (MI) was induced by ligation of left coronary artery of severe combined immunodeficient mice before 2 × 105 iMSCs or cell-free saline were injected into peri-infarcted anterior free wall. Sham-operated animals received no injection. Global and regional myocardial function was assessed serially at 1-wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 37 publications
8
22
0
Order By: Relevance
“…The advantages and limitations of each stem cell with regard to the possible emergence of ethical concerns (symbolized by ¥), the invasiveness and collection (from + to ++++), the isolation procedure, the abundance (from + to ++++), expansion and proliferation rate, the transdifferentiation capacity, the paracrine effects or/and cardiomyogenic potential, the survival and engraftment capacity as well as the immunogenic, oncogenic or teratogenic risks is given in the accessory side tables. The left table abridges bone marrow-derived stem cells [3,[19][20][21]27,28], cortical bone-derived stem cells [32,33], adipose tissue-derived stem cells [34,37,39,41] and gestation-related stem cells [42][43][44][45][46][47][48][49]51,54] and the right table abridges cardiac stem cells [57,59,60], skeletal muscle stem cells [62,63,66] and induced pluripotent stem cells [67,[69][70][71]. The human body scheme was constructed with images sourced from Servier Medical Art (http://www.servier.com/ Powerpoint-image-bank) and Cientic website (http://www.cientic.com/).…”
Section: Adipose Tissue-derived Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…The advantages and limitations of each stem cell with regard to the possible emergence of ethical concerns (symbolized by ¥), the invasiveness and collection (from + to ++++), the isolation procedure, the abundance (from + to ++++), expansion and proliferation rate, the transdifferentiation capacity, the paracrine effects or/and cardiomyogenic potential, the survival and engraftment capacity as well as the immunogenic, oncogenic or teratogenic risks is given in the accessory side tables. The left table abridges bone marrow-derived stem cells [3,[19][20][21]27,28], cortical bone-derived stem cells [32,33], adipose tissue-derived stem cells [34,37,39,41] and gestation-related stem cells [42][43][44][45][46][47][48][49]51,54] and the right table abridges cardiac stem cells [57,59,60], skeletal muscle stem cells [62,63,66] and induced pluripotent stem cells [67,[69][70][71]. The human body scheme was constructed with images sourced from Servier Medical Art (http://www.servier.com/ Powerpoint-image-bank) and Cientic website (http://www.cientic.com/).…”
Section: Adipose Tissue-derived Stem Cellsmentioning
confidence: 99%
“…1), though these cells are readily available, as their progenitors are somatic cells, bypassing the ethical concerns related to the collection of ESC [67][68][69][70]. Again, paracrine activity is believed to be the main mechanism of iPSC action through, for instance, angiogenesis stimulation [71].…”
Section: Induced Pluripotent Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different cell types, including mesenchymal stem cells (MSCs), cardiac progenitor cells (CPCs), cardiosphere-derived cells (CDCs), embryonic stem cells (ESCs), and induced pluripotent stem cells (iPSCs), have been investigated in both pre-clinical and clinical studies 5-11 , but overall the studies yielded variable results and the basic mechanisms that underlie efficacious cell therapy remain unclear 12 . It has been proposed that the transplanted cells are able to release angiogenic factors, protect cardiomyocytes from apoptotic cell death, and recruit resident cardiac stem cells that facilitate cardiac repair 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that this method seems to be unrelated to TCs, it was observed that 4 weeks after transplantation endogenous and exogenous cardiac TCs appeared and intermingled in the infarction zone. What is the most important is the fact that recovery of their network in ischaemic area coincided with increased angiogenesis and improvement of myocardial strain (43,44).…”
Section: Current Achievements Of Tcs-related Experimental Therapiesmentioning
confidence: 99%